2015
DOI: 10.1155/2015/328642
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Manufactured Chinese Herbal Formula for Knee Osteoarthritis: Insights from a Systematic Review

Abstract: Objective. To assess the current clinical evidence of manufactured Chinese herbal formulae (MCHF) for knee osteoarthritis (KOA). Methods. Seven databases were searched from inception to May 2015. Eligible randomized controlled trials investigating the effectiveness of MCHF for KOA were included. Data extraction, methodological assessment, and meta-analyses were conducted according to the Cochrane standards. Results. A total of 17 kinds of MCHF were identified from the twenty-six included trials. Meta-analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Alternative medicine is popular among Asian older adults (56) as it is believed to be harmless [56,57]. The effectiveness of traditional remedies for knee pain, however, remains controversial [58][59][60][61][62]. The reluctance to accept painkillers appeared to lead to activity avoidance and functional limitations, which are the primary concerns of our older persons with KOA as well as being worried about not being able to observe religious rituals involving kneeing or sitting cross-legged.…”
Section: Plos Onementioning
confidence: 99%
“…Alternative medicine is popular among Asian older adults (56) as it is believed to be harmless [56,57]. The effectiveness of traditional remedies for knee pain, however, remains controversial [58][59][60][61][62]. The reluctance to accept painkillers appeared to lead to activity avoidance and functional limitations, which are the primary concerns of our older persons with KOA as well as being worried about not being able to observe religious rituals involving kneeing or sitting cross-legged.…”
Section: Plos Onementioning
confidence: 99%
“…Under this circumstance, complementary and alternative medicine represented by Chinese herbal medicine has become a popular treatment option for knee OA patients around the world. 9,10 In our previous study, 11 to investigate the preliminary effect of SSG on experimental OA, we have demonstrated that prepared SSG as feed could improve cartilage degeneration and cartilage matrix degradation, decrease the levels of inflammatory mediators in synovial fluid of osteoarthritic rabbit knee joints, suggesting SSG showed potential benefits for knee OA. Nevertheless, the active components of SSG and their pharmacological activities are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“… 3 KOA is more important not only for its high prevalence rate compared with other types of OA but also for its presentation at earlier age groups particularly in younger age groups of obese women. 4 , a) , b) The KOA-related symptoms have a major impact on subject social and physical wellbeing, and KOA is expected to be the fourth leading cause of disability in 2020. 5 …”
Section: Introductionmentioning
confidence: 99%